Outcome of Re-Using radiofrequency ablation catheter for varicose veins treatment - Edwin Stephen; Albert Abhinay Kota; Deepak George John; Vimalin Samuel; Andrew Dheepak Selvaraj; Prabhu Premkumar; Sunil Agarwal (Indian Journal of Vascular and Endovascular Surgery, 2020)
Objective: The objective of the study is to evaluate the success of re-use by assessing the recanalization rates following radiofrequency ablation (RFA) with Closure Fast® catheter in patients with symptomatic varicose veins. Methods: This retrospective study approved by the institutional review board analyzed the occlusion rates of the great saphenous vein (GSV) in patients who underwent RFA between January 1, 2015, and December 31, 2016. A record of the number of times the RFA catheter was re-used was maintained. The catheter was used for a maximum of five systems. Follow-up was performed postoperatively at 1 week and 6 months with an ultrasound to assess failure by looking for recanalization. Results: In this study, 272 GSV endoablations (RFA) were performed in 238 patients. The mean age was 47.68 (standard deviation ± 13.05). Majority of the patients were male (76.9%). 27.3% (73 GSV) of the venous systems received a first fire with the RFA catheter. At the first follow-up on week 1, 97.7% (266 GSV systems) had complete occlusion, 2.3% (6 GSV systems) had partial recanalization, and none had complete failure. Recanalization rates at 1 week with 1st, 2nd, 3rd, 4th, and 5th re-use were 0%, 2%, 2%. 4.1%, and 3.8%, respectively. At 6-month postoperative follow-up, 96.5% (250) had complete occlusion, 2.7% (7) had partial recanalization, and 0.8% (2) had complete recanalization. Recanalization rates at 6 weeks with 1st, 2nd, 3rd, 4th, and 5th re-use were 1.4%, 2.1%, 2.3%. 6.4%, 5.9% respectively. There was no statistical significance with the recanalization rates at 1st week and at 6 weeks. 4.2% (10) of the patients were lost to follow-up. None of the patients had any complications. Conclusion: The results of GSV occlusion rates are encouraging when the RFA catheter was re-used and cut the cost of treatment substantially, thereby making RFA ablation more affordable to the common human.